ANALISIS KINERJA KOMPOR GAS BERBAHAN BAKAR DIMETHYL ETHER DENGAN VARIASI DIAMETER LUBANG ANGIN PADA NOSEL - Sutrisno, Seno; Sigit Iswahyudi; Rany Puspita Dewi (Jurnal Rekayasa Mesin, 2024)
The use of a vent on a gas stove affects the mixing of air with fuel. This study examines the effect of different vent diameters on the performance of Dimethyl Ether (DME) gas-fueled stoves. A nozzle with variations in vent diameter of 3 mm, 2 mm, 1 mm, and no vent with a nozzle diameter of 0.96 mm at each vent. Installed on the fuel ignition system, the flame, heat intake, and combustion efficiency were tested. From the test results at a pressure of 280 mmH2O, the highest flame noise value after shutdown was obtained at the nozzle with a 1 mm vent which amounted to 64.2 dB, the highest heat intake value at the nozzle with a 1 mm vent which amounted to 1.6625 kW, and the highest efficiency value at the nozzle with a 3 mm vent which amounted to 59.135%.